Effectiveness of Giving Ambon Banana, Avocado and Honey Juice on Increasing Hemoglobin (Hb) Levels in Pregnant Women - Retno Palupi Yonni Siwi; Erma Retnaningtyas; Anggrawati Wulandari; Nur Yeny Hidajaturrokhmah; Era Pebriana (Universitas STRADA Indonesia, 2025)
Background: Anemia in pregnancy is a condition in which the mother has a hemoglobin level below 11 gr% in the first and third trimesters, and a level below 10.5 gr% in the second trimester. Most anemia in pregnancy is caused by iron deficiency and acute bleeding. Purpose: The effectiveness of giving ambon banana, avocado and honey juice to increase hemoglobin levels in pregnant women. Methods: True experiment with pretest and posttest control group design. The sampling technique used was purposive sampling obtained a sample of 34 respondents, namely 17 control and intervention groups. Analysis using the Independent t-test. Results: The Independent t-test statistical test resulted in p=0.001<0.05, meaning there was an influence of Ambon Banana, Avocado and Honey juice on increasing hemoglobin levels in pregnant women. Conclusion: Giving ambon banana, avocado and honey juice is effective in increasing hemoglobin levels in pregnant women. Bananas contain iron which will stimulate the production of hemoglobin in the blood. Avocados have important nutrients, namely vitamin C, vitamin E, vitamin K, iron, folic acid, potassium and quite high levels of calories and fat which are useful as a source of energy. Honey contains important minerals which help form hemoglobin.